The quadruple sustainability: Economic, social, environmental, and family - Forés, Beatriz; Clemente-Almendros, José Antonio (Competitiveness, Organizational Management, and Governance in Family Firms, 2022)
This chapter analyzes the relationship between ownership structure and sustainability performance adopting the socioemotional wealth approach. This work extends previous literature on the topic by considering the three dimensions of sustainability performance: economic, social, and environmental. Analysis with the matching technique revealed that being a family firm has a positive effect on economic profitability, growth sales, employees training and commitment, investment in R&D, environmental commitment, and cooperation agreements with external partners. The authors use a sample of Spanish firms operating in the tourism industry.
Keywords: quadruple sustainability; economic; social; environmental; family; Scopus(2)